Jürgen Moltmann: Persahabatan Sebagai Antisipasi Kepenuhan Harapan - Antonius Denny Firmanto (Seri Filsafat Teologi, 2020)
Jürgen Moltmann’s theology of hope enacts the idea of hope as the foundation of friendship. Those who want to live in a friendship should be open to each other, acknowledging that misapprehension and misunderstanding are possible in a friendship journey. To achieve the value of salvation in experiencing friendship, one needs to have the courage to turn or direct his/her vision to the experience of God. God Himself has experienced that His logging to reach man and have good relationship with His people is obstructed by man’s stubbornness to refuse His love. Jesus’ passion and death is the peak of man’s refusal to God’s plan of love. Similarly, the faithful is able to open his/her heart and direct his/her vision to his/her friends only. The openness of one’s heart has the character of inviting and waiting until the right time his/her friends have the courage to open themselves in a salvaging relationship. Until the time comes, for the faithful, the friendship with God is comforting and supporting in every failure and rejection. The task of every Christian is to facilitate and mend the relationship. Moltmannian’s hope shows that the relationship between God, the Eschatology, and hope, is manifested in a commitment to inclusivity; the ministry to those in need, environment concern, and faithfulness to those who are poor and marginalized.